Personalized education approach based on cognitive psychology for endoscopic diagnosis: A multicenter randomized trial - Kentaro Mochida; Fumiaki Ishibashi; Masamichi Yuzawa; Daisuke Suto; Toshihiro Nishizawa; Yasunari Sakamoto; Mikinori Kataoka; Mitsuru Esaki; Chika Kusano; Takuji Gotoda; Kenichi Konda; Jun Arimoto; et al. (PLoS ONE, 2025)
The learning curve for endoscopic diagnosis varies, and an optimal educational strategy is not available. Working memory (WM) refers to an individual’s ability to store and process information quickly and simultaneously. This study aimed to determine whether educational methods, optimized by individual WM, facilitate learning about endoscopic diagnoses. In the development phase, the standard WM profile for general endoscopists was determined by 79 endoscopists. In the validation phase, 60 trainees from four Japanese institutions were assessed for visuospatial or verbal WM dominance, based on the standard WM profile, and randomly assigned to receive matched (Matched-E group) or unmatched (Unmatched-E group) education. In the Matched-E group, the visuospatial and verbal WM-dominant trainees learned the endoscopic diagnosis of colorectal polyps by pattern recognition and through the description text of narrow-band imaging classification, respectively. In the Unmatched-E group, participants received education that was opposite to their dominant WM type. The diagnostic accuracy of the endoscopic diagnosis of colorectal polyps was compared between the groups after each educational session. Among the 60 trainees, 40 (21 in Matched-E and 19 in Unmatched-E) completed the validation test. The diagnostic accuracy was significantly higher in the Matched-E group than that in the Unmatched-E group (61.6% vs. 53.9%, P = 0.008). The diagnostic accuracy for non-neoplastic lesions was higher in the Matched-E group than that in the Unmatched-E group (68.0% vs. 48.4%, P = 0.002), whereas it did not differ for adenoma, intramucosal cancer, or invasive cancer. The personalized education based on the WM profile facilitated learning endoscopic diagnosis.